(untitled) (Eurasian Scientific Herald, 2023)
The current era calls for citizens who are not only academically sound but also imbued with patriotic values. Educating young people in the spirit of patriotism becomes a crucial challenge for teachers, especially in a technologically advanced, globalized world. Traditional pedagogical methods are not always effective in instilling patriotism in students, as they tend to focus only on the academic aspects. However, new pedagogical methods can provide innovative solutions to this challenge. This abstract examines new pedagogical methods of educating young people in the spirit of patriotism, encompassing the use of technology, art, culture and more personalized approaches. These approaches entail a holistic learning experience that not only enhances students’ academic skills but also aids in their character development, thereby producing well-rounded citizens capable of embodying patriotic ideals.